RADIO STATIONS AND COMPLIANCE WITH NIGERIAN BROADCASTING CODE IN SOUTH-EAST NIGERIA - Ebenezer, Adaeze; Ihechu, Innocent Paschal; Udoh, Ima Saviour (IJRDO - Journal of Social Science and Humanities Research, 2022)
ABSTRACT This sought to assess the compliance with the political provisions of Nigeria Broadcasting Code by radio stations in South East Nigeria. The major objective of the study was to ascertain the level of compliance with the political provisions of code by radio stations in South East Nigeria. The Agenda Setting Theory and Social Responsibility Theory were employed as a theoretical framework for the study. The population of the study was 383 being the total number of workers in the 45 radio stations in south east Nigeria. Since the number was considered small and manageable, the researcher conducted a census; there was no sampling as all the members of the population were studied. The instrument for data collection was the questionnaire. At the end of analysis, it was found that a higher percentage agreed to the issue of compliance with the Nigeria broadcasting code. It was also found that the stations complied with political provisions in the areas of news and current affairs and political jingles. It was therefore concluded that there was a high level compliance by radio stations in South East Nigeria with the political provisions of the Nigerian Broadcasting Code. The researcher therefore recommends that the station managers should ensure that their staff especially the on air staff be in line with the NB Code so as to ensure sustained compliance.